2023
DOI: 10.3390/ma16020522
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Fines Content on Durability of High-Strength Manufactured Sand Concrete

Abstract: Manufactured sand is one of the effective ways to alleviate the extreme shortage of natural sand in the construction industry. This paper uses granite and limestone manufactured sand to study the effect of high fines content on the durability of high-strength manufactured sand concrete, and analyzes its influence mechanism by combining macro and micro test methods. The results show that the carbonation depth of manufactured sand concrete is the smallest when the fines content is 10%. When the fines content is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…The study highlights the potential for further enhancements in flowability and tensile strength. Zheng et al (2023) [17] examines the high-strength M-sand concrete for the durability characteristics, the impact of high fines content was assessed for the mix prepared with the incorporation of granite and limestone M-sand. The study finds that a fines content of 10% yields the smallest carbonation depth and effectively improves chloride and sulphate impermeability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The study highlights the potential for further enhancements in flowability and tensile strength. Zheng et al (2023) [17] examines the high-strength M-sand concrete for the durability characteristics, the impact of high fines content was assessed for the mix prepared with the incorporation of granite and limestone M-sand. The study finds that a fines content of 10% yields the smallest carbonation depth and effectively improves chloride and sulphate impermeability.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The granite powder was beneficial regarding the high-strength concrete durability with manufactured sand within a certain range of replacements. However, too-high values of fine powder could inhibit the hydration of the cement and then adversely affect the durability of the resulting concrete [20]. Shen et al found that the particle shape and surface texture of manufactured sand had less influence on the performance of the concrete than that of stone powder [21].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al [ 26 ] experimentally determined that the depth of reinforcement carbonation and the probability of corrosion initially decreased, then increased with the increasing proportion of stone powder, reaching a minimum carbonation depth at 7% stone powder content. Zheng et al [ 27 ] showed that the carbonation depth of manufactured sand concrete is the smallest when the fines content is 10%. When the fines content is less than 15%, the chloride and sulfate impermeability of concrete are improved effectively.…”
Section: Introductionmentioning
confidence: 99%